PENDIDlKAN POLITIK BAGI WANITA DA·LAM ERA REFORMASI 8AAT INI - Sri Pujiastuti Sri Pujiastuti (LPMPP Universitas Negeri Yogyakarta, 2001)
In tile present era (Jjo rejorn1s ,11ere is considerable political tension and certainpolitical education transforming current visi()n..ój'politics needs to be conducted as aneffort to decrease tile political tenSi()1l. It will present a new vision ofpolitics 10ltgedfor bytJ10se WIlD dearly love peace. In thL\